Pengaruh Akuntabilitas Dan Transparansi Pengelolaan Keuangan Daerah Terhadap Kinerja Pemerintah Daerah Kabupaten Gorontalo - Veronica Wongkar, Filly; ., Saprudin; Masiaga, Novaliastuti; Abdullah, Julie; Nurannisa Hippy, Mega (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to analyze the influence of accountability and transparency in the management of regional finances on the performance of the Gorontalo District Government. The research employs a multiple linear regression model to examine the relationship between independent and dependent variables. The results indicate that accountability has a significant positive impact on government performance; higher levels of accountability in governance lead to better government performance. Transparency also shows a significant positive effect on government performance; openness and transparency in governance contribute to enhancing government performance. Both accountability and transparency are critical factors determining government performance; enhancing both accountability and transparency together will significantly improve government performance